Peran Teknologi Informasi dalam Meningkatkan Efisiensi Pengadaan Barang dan Jasa di Organisasi Non-Profit - Apprilisda Ranica Putri; Devi Maria Saadah; Wulan Alviena Putri Utami; Sigit Djalu Purwoko (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
Managing efficiency in the procurement of goods and services in non-profit organizations is a crucial aspect in supporting the continuity and sustainability of social missions. In the era of globalization and digital transformation, the role of Information Technology (IT) cannot be ignored. Non-profit organizations are often faced with challenges in improving procurement efficiency, including managing limited resources and limited access to the latest information. The main objective of this research is to analyze and document the impact of applying Information Technology in improving the efficiency of procurement of goods and services in non-profit organizations profit. The research design that can be used is a case study or field experiment. The results of this research show that the adoption of Information Technology (IT) in the procurement of goods and services in non-profit organizations makes a significant contribution to operational efficiency and achieving humanitarian goals. This success depends not only on the technology itself, but also on the organization's commitment to continuously developing IT policies and infrastructure.